Diphtheria seroprotection among Indonesian children: Community Health Surveys Riskesdas 2007, 2013 and 2018 - Monica Dwi Hartanti; Sunarno Sunarno; Novaria Sari Dewi Panjaitan; Armedy Ronny Hasugian; Rita Marleta Dewi; Sarwo Handayani; Masri Sembiring Maha; Tubagus Ferdi Fadilah; Firda Fairuza; Nathalia Ningrum; Meiriani Sari; Dita Setiati; et al. (PLoS ONE, 2026)
Diphtheria remains a public health concern in Indonesia despite long-standing inclusion of diphtheria-containing vaccines in the national immunization program. This study assessed temporal trends in diphtheria immunity among Indonesian children aged 1–14 years, identified vulnerable age groups, and examined factors associated with seroprotection. We analyzed diphtheria IgG antibody data measured by ELISA from the Indonesian Community Health Surveys (Riskesdas) conducted in 2007, 2013, and 2018. The analysis included 6,622 children (2007), 7,110 (2013), and 7,203 (2018). Bivariate and multivariate logistic regression analyses were performed to identify determinants of seroprotection. Across all surveys, diphtheria IgG levels were lowest at ages 1–6 years, increased at ages 7–10 years, and declined again from age 11 years onward. Overall seroprotection ranged from 71.1% to 83.6%, with a two- to threefold increase in long-term protection observed in 2018 compared with 2007 and 2013. In multivariate analyses, complete DTP immunization consistently remained the strongest independent predictor of seroprotection among children aged 1–4 years (p < 0.05). Among children aged 1–14 years, maternal education (Riskesdas 2007) and household economic status (Riskesdas 2018) were also associated with seroprotection. Following the introduction of the DTP4 booster, higher diphtheria IgG concentrations (GMC 0.48 IU/mL to 0.77 IU/mL) were observed among children aged 1–2 years old in 2018 compared with earlier surveys (GMC 0.18 IU/mL to 0.33 IU/mL). Diphtheria immunity among Indonesian children remains suboptimal, with the highest vulnerability at ages 5–6 years and evidence of waning immunity after ten years of age. Ensuring complete routine DTP immunization is critical, and booster strategies may be considered to sustain long-term population immunity.